Viewing Teacher Motivation in the Ghana Education Service through a Postcolonial Lens - Inusah Salifu; Joseph Seyram Agbenyega (Arizona State University, 2013)
In recent times, quality teaching has become the focus of many education systems including that of Ghana, and yet little attention has been given to teacher motivation that could ensure quality teaching and improved learning outcomes. Drawing on contemporary literature on issues associated with teacher motivation, this conceptual paper critically examines and analyses the context of teacher motivation and professional practice in the Ghana Education Service. It addresses the questions: What are the working conditions that are causing a lack of motivation among teachers in public pre-tertiary schools in Ghana? How can teacher motivation in the Ghanaian context be analyzed using postcolonial theoretical concepts? It concludes with some recommendations that can lead to improvements in teacher conditions and motivation in Ghana.